2020
DOI: 10.1097/eja.0000000000001391
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged postoperative cerebral oxygen desaturation after cardiac surgery

Abstract: BACKGROUND Near-infrared spectroscopy (NIRS) is used routinely to monitor cerebral tissue oxygen saturation (SctO2) during cardiopulmonary bypass (CPB) but is rarely employed outside the operating room. Previous studies indicate that patients are at risk of postoperative cerebral oxygen desaturation after cardiac surgery. OBJECTIVES We aimed to assess perioperative and postoperative changes in NIRS-derived SctO2 in cardiac surgery patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…A good example has been demonstrated in a recent study in post cardiac-surgical patients which showed a progressive postoperative decline in rSO2 from the day of surgery until day 7 with 97% of patients below baseline value at discharge. 9 A given value at one time point was not associated with clinical deterioration. Hence, it seems appropriate to set an alarm value on NIRS to look at the determinants of brain oxygenation in a dynamic manner.…”
Section: Conflicts Of Interest : Nonementioning
confidence: 81%
“…A good example has been demonstrated in a recent study in post cardiac-surgical patients which showed a progressive postoperative decline in rSO2 from the day of surgery until day 7 with 97% of patients below baseline value at discharge. 9 A given value at one time point was not associated with clinical deterioration. Hence, it seems appropriate to set an alarm value on NIRS to look at the determinants of brain oxygenation in a dynamic manner.…”
Section: Conflicts Of Interest : Nonementioning
confidence: 81%
“…Notably, cerebral desaturations continue to occur during the postoperative ICU stay in a large subset of patients [38,39]. A recent study showed prolonged postoperative cerebral desaturation after cardiac surgery with cardiopulmonary bypass (CPB), but not after noncardiac surgery [40]. Therefore, there is a need and growing interest in extending the monitoring of ScO 2 to the postoperative phase, even though the evidence is still limited [41] and insufficient to recommend postoperative monitoring [37 ▪▪ ].…”
Section: Introductionmentioning
confidence: 99%